2015
DOI: 10.1007/s11999-014-3801-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Knee and Hindfoot Deformities in Advanced Knee OA: Compensatory Hindfoot Alignment and Where It Occurs

Abstract: Background Many patients undergoing TKA have both knee and ankle pathology, and it seems likely that some compensatory changes occur at each joint in response to deformity at the other. However, it is not fully understood how the foot and ankle compensate for a given varus or valgus deformity of the knee. Questions/purposes (1) What is the compensatory hindfoot alignment in patients with end-stage osteoarthritis who undergo total knee arthroplasty (TKA)? (2) Where in the hindfoot does the compensation occur? M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
173
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 16 publications
(33 reference statements)
4
173
0
1
Order By: Relevance
“…A few studies involving patients with knee osteoarthritis undergoing TKA, have demonstrated that varus deformity of the knee is associated with a valgus hindfoot [3,5,6]. Recently, in patients with end-stage knee osteoarthritis, Norton et al also demonstrated that a valgus knee tends to be associated with a varus hindfoot, and they indicated that this correlation was stronger in patients with larger knee deformities [6]. This finding coincides with our finding that a correlation exists between the knee and hindfoot alignments only in knees with a Larsen grade ≥4.…”
Section: Mod Rheumatol Downloaded From Informahealthcarecom By Mcmasmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies involving patients with knee osteoarthritis undergoing TKA, have demonstrated that varus deformity of the knee is associated with a valgus hindfoot [3,5,6]. Recently, in patients with end-stage knee osteoarthritis, Norton et al also demonstrated that a valgus knee tends to be associated with a varus hindfoot, and they indicated that this correlation was stronger in patients with larger knee deformities [6]. This finding coincides with our finding that a correlation exists between the knee and hindfoot alignments only in knees with a Larsen grade ≥4.…”
Section: Mod Rheumatol Downloaded From Informahealthcarecom By Mcmasmentioning
confidence: 99%
“…The impact of hindfoot alignment on the mechanical axis of the lower limb has been recently elucidated [3,5,6,[23][24][25]. The range of motion of the subtalar joint is reportedly as much as 5 -10 ° of inversion and 25 -30 ° of eversion For personal use only.…”
Section: Mod Rheumatol Downloaded From Informahealthcarecom By Mcmasmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[27][28][29]41 HFA measures based on 2D radiographs are flawed by many anatomical and operator-related bias, which have been extensively investigated in the literature. * These include projection and rotational issues, 3,22 mostly with regards to the use of the tibia as a reference axis.…”
Section: Introductionmentioning
confidence: 99%
“…Beveik visų amžiaus grupių pacientų buvo po lygiai. Priešingai nei kitų autorių duomenys, didesnę mano operuotų pacientų dalį sudarė suaugę ir net vyresnio amžiaus pacientai (4,19). Vaikų ir jaunimo (iki 20 metų) buvo tik 19,1%.…”
Section: Diskusijaunclassified